Penerapan Media Pembelajaran Ular Tangga Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas VIII Di SMPN 1 Sakra - Susilawati Susilawati; Izmiatul Amnah; Rico Aprial Sagali; Siti Humairoh (Alpatih Harapan Semesta, 2025)
This study aims to improve students’ learning outcomes in Social Studies (IPS) through the application of the Snakes and Ladders learning media in class VIII-H of SMPN 1 Sakra in the 2025/2026 academic year. The type of research used is Classroom Action Research (CAR) employing the Kemmis and Mc. Taggart model, which consists of four stages: planning, action implementation, observation, and reflection, conducted in two cycles. The subjects of this study were 21 students of class VIII-H at SMPN 1 Sakra. Data collection techniques included observation, questionnaires, tests, documentation, and field notes. The results showed that the use of Snakes and Ladders learning media could increase students’ motivation and learning outcomes. This was evidenced by an improvement in the average learning score from 86.19 in the first cycle to 96.23 in the second cycle, as well as an increase in learning mastery from 85.71% to 100%. The improvement occurred because the learning process became more engaging, interactive, and enjoyable, allowing students to learn while playing and actively participate in classroom activities. Thus, the Snakes and Ladders learning media proved effective in improving students’ learning outcomes in Social Studies, particularly in economic topics. This media can serve as an innovative alternative in the learning process to create a more meaningful, active, and enjoyable learning environment for students.